The Spectral Method for the Cahn-Hilliard Equation with Concentration-Dependent Mobility - Shimin Chai; Yongkui Zou (Journal of Applied Mathematics)
This paper is concerned with the numerical approximations of the Cahn-Hilliard-type equation with concentration-dependent mobility. Convergence analysis and error estimates are presented for the numerical solutions based on the spectral method for the space and the implicit Euler method for the time. Numerical experiments are carried out to illustrate the theoretical analysis.